SOCIAL MEDIA AND MENTAL HEALTH - Alfathron, Bramastian Samudro (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2024)
Introduction – For many young people dealing with mental illness, social media has bas become an important part of their life to dealing with mental illness. Social media is a wide term that refers to mobile platforms and the web that allow people to communicate with one another in a network. Instagram Facebook, Twitter, Snapchat, etc are some of the most popular social media platforms among young people. Methods – This paper results from literature that talks about social media and mental health. Results – Social media have a lot of positive content and negative content. Many young people appear to use social media to share their personal experiences, look for information about mental health, and give and get support from others who have similar or same mental health challenges experiences. Discuss – The positive impact of social media will affect young people’s promotion of mental health and awareness about mental health. The positive impact of social media has a benefit where they can find social support about mental health. Social media also can make young people or individuals receive negative peer feedback in social media may have negative consequences for psychological development and well-being. Conclusion – Besides the many positive impacts in social media uses, social media has a lot of negative impacts with the consequences. Negative content such as online harassment, sexting, and cyberbullying will hurt mental health which will cause young people stress, anxiety, and depression. Keywords: social media, mental health, young.